Synthesis and Characterisation of {PdNO}10 Pincer Complexes - Sinclair, Matthew J.G.; Roig, Nil; Tsoureas, Nikolaos; Alonso, Mercedes; Chaplin, Adrian B. (European Journal of Inorganic Chemistry, 2025)
The synthesis and characterisation of two square planar {PdNO}10 pincer complexes of the form [Pd(pincer)(NO)]+ (pincer = 2,6-(tBu2PCH2)2C5H3N, 1; 2,6-(tBu2PO)2C5H3N, 2) are reported. These complexes are readily isolated by phosphine substitution of T-shaped [Pd(PtBu3)2(NO)]+ 3 in THF and the bent nitrosyl coordination mode observed in 3 is retained, as evidenced by X-ray diffraction (∠PdNO ∼ 120°), IR spectroscopy and analysis of isotopically enriched samples by 15N NMR spectroscopy. Effective oxidation states of Pd0/NO+ are calculated for 1–3 and nitrosyl coordination is principally attributed to metal-centred σ-bonding, with supplementary π-backbonding. Computational analysis, however, indicates that the Pd−NO bonds in 1 and 2 have greater PdI/NO• character and σ-bonding is more prominent than in 3. These differences in bonding are manifested experimentally in more red-shifted nitrosyl stretching frequencies and the propensity of 1 and 2 to react with dichloromethane to afford palladium(II) chloride derivatives.
Keywords: Electronic structure; Energy decomposition Analysis; Nitrosyl ligands; Palladium; Pincer ligands